2002
DOI: 10.1002/mrd.10243
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of adult and prepubertal mouse oocytes to undergo embryo development in the presence of cysteamine

Abstract: The present study was carried out to study de novo glutathione (GSH) synthesis and to evaluate the effect of stimulating GSH synthesis during in vitro maturation (IVM) of adult and prepubertal mouse oocytes on the embryo developmental rate. Adult (8 weeks old) and prepubertal mice (24-26 days old) were primed with 5 IU of PMSG and oocytes were retrieved from the ovary 48 hr later for IVM. After IVM (18 hr) Cumulus oocyte complexes (COC) were in vitro fertilized (IVF) and in vitro culture (IVC) in order to obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 32 publications
(46 reference statements)
7
20
0
Order By: Relevance
“…These results are in agreement with other reports showing that supplementation with Cys during IVM did not influence the rate of cleavage (40,41) but enhanced embryo development (9,10,17,42). Several studies have shown that Cys increases cytoplasmic glutathione levels in bovine and ovine oocytes (17,20,43,44) and that Cys has a positive influence on embryo development (44). It is likely that the enhanced glutathione concentration promotes early embryo development by facilitating the completion of oocyte cytoplasmic maturation (10,41,42).…”
Section: Figuresupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in agreement with other reports showing that supplementation with Cys during IVM did not influence the rate of cleavage (40,41) but enhanced embryo development (9,10,17,42). Several studies have shown that Cys increases cytoplasmic glutathione levels in bovine and ovine oocytes (17,20,43,44) and that Cys has a positive influence on embryo development (44). It is likely that the enhanced glutathione concentration promotes early embryo development by facilitating the completion of oocyte cytoplasmic maturation (10,41,42).…”
Section: Figuresupporting
confidence: 90%
“…Gasparrini et al (41) showed that supplementation with Cys during IVM of buffalo oocytes significantly enhanced cytoplasmic glutathione content after maturation and subsequently improved embryo development. A study by de Matos et al (44) showed a positive effect of Cys in IVM on blastocyst development in adult mice, but this effect was not observed in oocytes recovered from prepubertal mice. Furthermore, Abeydeera et al (7) and Brad et al (47) reported no significant difference between the rate of nuclear maturation of porcine oocytes matured in UDMM (medium containing follicular fluid) versus those matured in DMM supplemented with Cys and EGF.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…cattle [8], pigs [1], mice [9]. In the present study, β-mercaptoethanol significantly increased GSH content in follicular and luteal oocytes during IVM.…”
Section: Discussionsupporting
confidence: 53%
“…In cattle and pigs, oocytes from prepubertal donors display poor meiotic maturation and embryo development compared to oocytes from adult females (Marchal et al, 2001;Salamone et al, 2001;de Matos et al, 2003;Grupen et al, 2003;Sherrer et al, 2004). Consistent with their lesser meiotic and developmental potential, oocytes from sexually immature females display morphological, biochemical and physiologic alternations or anomalies that could partially account for their reduced competence.…”
Section: Effect Of Maternal Age and Breeding Season On Embryo Developmentioning
confidence: 99%